PERBANDINGAN PENERAPAN CTL DAN RME DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH - Sulystiani, Fida; Agustan Syamsuddin; Mukhlis, Mukhlis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to compare the problem-solving abilities student activities between the utilization of Contextual Teaching and Learning (CTL) and Realistic Mathematics Education (RME) approaches, both partially and simultaneously. The study was conducted at the SPF SD Inpres Bertingkat Bara-Baraya II Educational Unit using a quantitative approach employing a quasi-experimental design known as nonequivalent control group design. The research population comprised all sixth-grade students of the SPF SD Inpres Bertingkat Bara-Baraya II for the academic year 2023/2024, with a sample size of 44 students selected through simple random sampling and divided into two experimental groups. Data were collected through tests and observations, followed by analysis using descriptive statistical analysis, inferential analysis, and hypothesis testing through Independent Sample T tests and Manova. The research findings indicate no significant differences in problem-solving abilities, mathematical communication, and student activities between the two instructional approaches, both partially and simultaneously. The significance levels for problem-solving, mathematical communication, and student activities were 0.161, 0.308, and 0.523, respectively, all exceeding 0.05, indicating no significant differences. Additionally, the results of the Wilks’ Lambda statistical test yielded a significance level of 0.413 > 0.05, indicating no significant differences simultaneously across the three observed variables. Consequently, it can be concluded that there are no significant differences in problem-solving abilities, mathematical communication, and student activities between the utilization of CTL and RME approaches in mathematics education.